IMPLEMENTASI HUKUM WISATA HALAL BERDASARKAN QANUN ACEH NO. 8 TAHUN 2013 TENTANG KEPARIWISATAAN (Studi Penelitian Gampong Ujong Blang Kecamatan Banda Sakti Kota Lhokseumawe) - Yasir, Muhammad; Nasir, Muhamamad; Hamdani, Hamdani; Ath Thariq, Phoenna (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2025)
This study aims to determine how the implementation of halal tourism law based on Aceh Qanun Number 8 of 2013 concerning tourism in Ujong Blang Village, Banda Sakti Subdistrict, Lhokseumawe City, as well as what are the obstacles and solutions in implementing the qanun in Ujong Blang Village. Aceh Qanun No. 8/2013 on Tourism is a regulation established by the government of Aceh to regulate various aspects related to tourism development in Aceh Province. This Qanun aims to create a legal framework that supports the management and development of a sustainable tourism sector in accordance with the cultural values and norms of the people of Aceh. This research uses a qualitative method with an empirical juridical approach that is descriptive in nature. The research data is sourced from primary data, where data collection techniques are carried out through informants and obtained by interview, observation, and documentation. The results obtained from this study are the implementation of halal tourism law based on Aceh Qanun Number 8 of 2013 in Ujong Blang Village shows the strategic efforts of the departement of youth, sport, and tourism of Lhokseumawe City through coaching and socialization aimed at improving the understanding of the community and business actors about the concepts of halal tourism. Although there are adequate supporting facilities, obstacles such as lack of in-depth understanding of halal tourism, limited infrastructure in accordance with sharia standards, and lack of supervision are the main challenges. To overcome this problem, measures such as continuous education, training for business actors, strict law enforcement, cross-sector collaboration, and the preparation of strategic programs that support the effective implementation of halal tourism in Ujong Blang Village, Banda Sakti Subdistrict, Lhokseumawe City are needed.